Bending of thin-walled tubes - Peh, Jessica Jie Ying (2015)
Thin-walled structure is a very common engineering application as they provide efficiency in strength and cost at a minimized material usage. Therefore, there are many experiment and research studying the behaviors or thin-walled structures or tubes to further understand its material and mechanical properties so as to further improve it to be more efficient and effective. Unlike most research that used thin-walled tubes as their test specimen, this report focus on performing a four-point bending test on slit thin-walled tube in order to observe the behavior of this unique structure. Observing slit thin-walled tube behavior is to further understand how much force the structure can withstand and how it will react accordingly for other engineering usage in future. In order for the test specimen to undergo pure bending, materials selected must require certain level of high strength and ductility. Thus, mild steel and copper were selected for comparison. A further modification of an existing four-point pure bending mechanism was used. This modification was designed using SolidWorks for better secure and support of the slit thin-walled tube of this experiment. Furthermore, SolidWorks was also used to draft the size of slit thin-walled tube for machining into half and quarter slit thin-walled tubes. With all that, four-point bending test was carried out by Instron 5500 Universal Testing Machine and data was obtained from the Instron Bluehill Software. The slit thin-walled tubes were cut from tube of diameter 38mm and thickness 1.2mm. Different experiments were carried out based on its size (half & quarter) and position (U-bending, N-bending & C-bending) of the test specimen respectively. The obtained results had proven that C-bending is not feasible at all as it buckle at the contact point of the test specimen and the fixture as the pressure was localized at that point whereas U-bending and N-bending provides a nicer bending profile. Other than that, it had also proven that copper has higher material strength than mild steel as it required a might higher compressive load to obtain the same deflection as mild steel, which had resulted in having a higher bending moment than mild steel.